Icelandic Folklore and the Cultural Memory of Religious Change - Bryan, Eric Shane (Borderlines, 2021)
This book attempts to understand the origins and development of religious belief in Iceland and greater Scandinavia through the lenses of five carefully selected Icelandic folktales collected in Iceland during the nineteenth century. Each of these five stories has a story of its own: a historical and cultural context, a literary legacy, influences from beliefs of all kinds (orthodox and heterodox, elite or lay), and modalities (oral or written) by which the story was told. These factors leave an imprint- sometimes discernable, sometimes not- upon the story, and when that imprint is readable, the legacies and influences upon these stories come alive to illuminate a tapestry of cultural memory (that is, a society's perception of itself, its past, and its prospects for the future) and cultural development that might otherwise be hidden from the reader's eyes. So much is the aim of this book: to tell the story of five great stories.